Supporting Discovery and Inquiry: A Canadian Hospital's Approach to Building Research and Innovation Capacity in Point-of-Care Health Professionals. Issue 4 (October 2021) - Ruco, Arlinda; Nichol, Kathryn; Morassaei, Sara; Bola, Ruby; Di Prospero, Lisa
Abstract : Background and Objectives: Building capacity for research and innovation among point-of-care health professionals can translate into positive outcomes from the organization, staff, and patient perspective. However, there is not a widely accepted framework in place across academic hospitals to guide this work and measure impact. This article outlines one Canadian hospital's approach and provides a blueprint with appropriate indicators as a starting point and guide for organizations looking to develop and implement a practice-based research and innovation strategy. Methods: An adapted framework was utilized to measure and track progress toward achievement of research and innovation strategic goals. The framework outlines key domains for research and capacity development and appropriate metrics. Data are reported from a 4-year period (2014-2018). Results: The evaluation of the practice-based research and innovation portfolio identified several important factors that contribute to the success of embedding this strategy across a large academic teaching institution. These include using a collaborative leadership model, leveraging linkages, partnerships, and collaborations, and recognizing the academic contributions of health professionals engaging in research and innovation. Conclusions: Engaging those who provide care directly to patients and families in research and innovation is critical to ensuring high-quality health outcomes and patient experience. Creative and innovative funding models, collaborative leadership, and partnerships with key stakeholders to support research and innovation are needed to ensure sustainability.